2012
DOI: 10.1530/eje-11-0743
|View full text |Cite
|
Sign up to set email alerts
|

Association of hypogonadism with vitamin D status: the European Male Ageing Study

Abstract: Objective: Interrelationships between hormones of the hypothalamic-pituitary-testicular (HPT) axis, hypogonadism, vitamin D and seasonality remain poorly defined. We investigated whether HPT axis hormones and hypogonadism are associated with serum levels of 25-hydroxyvitamin D (25(OH)D) in men. Design and methods: Cross-sectional survey of 3369 community-dwelling men aged 40-79 years in eight European centres. Testosterone (T), oestradiol (E 2 ) and dihydrotestosterone were measured by gas chromatography-mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
152
9
16

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(184 citation statements)
references
References 32 publications
7
152
9
16
Order By: Relevance
“…[25] When viewed collectively, research suggests a relationship between hypogonadism and low VD. [20,43,44] Regrettably, there are few studies investigating T levels after VD supplementation. In an animal study on diabetic rats, it was demonstrated that treatment with VD for 12 weeks increased the serum level of T in treatment groups.…”
Section: Vitamin D and Endocrine Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] When viewed collectively, research suggests a relationship between hypogonadism and low VD. [20,43,44] Regrettably, there are few studies investigating T levels after VD supplementation. In an animal study on diabetic rats, it was demonstrated that treatment with VD for 12 weeks increased the serum level of T in treatment groups.…”
Section: Vitamin D and Endocrine Systemmentioning
confidence: 99%
“…In an animal study on diabetic rats, it was demonstrated that treatment with VD for 12 weeks increased the serum level of T in treatment groups. [26] In a clini- Abnormalities in calcium and phosphorus homeostasis [10,15] Bronchial asthma [4,7] Coronary artery disease [14,16] Erectile dysfunction [9,17,18] Heart failure [10,16] Hypertension [9,14] Hypogonadism [19][20][21][22] Impaired vascular endothelial and smooth muscle function [9,16] Increased immune or inflammatory response [23,24] Infertility [25,26] Metabolic syndrome [10,14,27] Osteoporosis [19,28,29] Peripheral vascular disease [15,30] Respiratory diseases [3,4] Wearing sunscreen clothes cal randomized controlled trial, which is the first on this topic in literature, Pilz et al [39] investigated the effect of VD supplementation on androgens in men. The results were significant and the researchers observed that overweight men with VDD had a clinically meaningful increase in serum T levels after VD supplementation for 1 year.…”
Section: Vitamin D and Endocrine Systemmentioning
confidence: 99%
“…В России недостаточность витамина D обнаружена у 78-83% населения [1,2]. Результаты по-следних эпидемиологических исследова-ний свидетельствуют о высокой частоте дефицита (недостаточности) витамина D у больных мужчин уроандрологического-профиля [3][4][5][6][7][8]. S. Pitman et al в 2011 году показали, что из 3763 исследуемых паци-ентов мужчин, у 68% имелся сниженный уровень витамина D [9].…”
Section: Abstract: Vitamin D Arterial Hypertension D-vitamin Deficiunclassified
“…Тюзикова, приблизительно у 50% россий-ских мужчин имеет место недиагностиро-ванная недостаточность витамина D, а у каждого третьего -тяжелый дефицит данного витамина [10]. При этом, наибо-лее часто дефицит витамина D у мужчин выявляется при ожирении, дефиците анд-рогенов, бесплодии и заболеваниях пред-стательной железы [3][4][5][6][7][8][9][10]. Получены убе-дительные доказательства, что дефицит витамина D у мужчин достоверно ассо-циируется с гипогонадизмом, ожирением, инсулинорезистентностью и сахарным диабетом 2 типа [11].…”
Section: Abstract: Vitamin D Arterial Hypertension D-vitamin Deficiunclassified
See 1 more Smart Citation